Space wars : quest for the deepstar [videorecording (DVD)] - Paré, Michael; Gruner, Olivier, 1960-; French, Sarah (Actress) (Uncork'd Entertainment, 2023)
A father and daughter team of space scavengers race against a band of evil mercenaries to reach a legendary lost freighter called the Deepstar. Along their trek through the universe, they encounter monsters, aliens, robots, and something even worse.